2016
DOI: 10.1016/j.micinf.2016.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Escherichia coli strains encoding colibactin colonize laboratory mice

Abstract: Escherichia coli strains have not been fully characterized in laboratory mice and are not currently excluded from mouse colonies. Colibactin (Clb), a cytotoxin, has been associated with inflammation and cancer in humans and animals. We performed bacterial cultures utilizing rectal swab, fecal, and extra intestinal samples from clinically unaffected or affected laboratory mice. Fifty-one E. coli were isolated from 45 laboratory mice, identified biochemically, and selected isolates were serotyped. The 16S rRNA g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 48 publications
2
26
1
Order By: Relevance
“…Thus it might be expected that IL-22 driven iNOS induction could lead to expansion of Enterobacteriaceae including those that carry genotoxins associated with cancer. In fact, we have observed the widespread presence of Colibactin producin E. coli within our colony 37 , and although not specifically quantified in this study, it is possible that Hh could promote DNA damage by enhancing colonization with these E. coli . The relationship between Hh-infection, dysbiosis, genotoxins, and DNA damage will clearly require further studies.…”
Section: Discussionmentioning
confidence: 66%
“…Thus it might be expected that IL-22 driven iNOS induction could lead to expansion of Enterobacteriaceae including those that carry genotoxins associated with cancer. In fact, we have observed the widespread presence of Colibactin producin E. coli within our colony 37 , and although not specifically quantified in this study, it is possible that Hh could promote DNA damage by enhancing colonization with these E. coli . The relationship between Hh-infection, dysbiosis, genotoxins, and DNA damage will clearly require further studies.…”
Section: Discussionmentioning
confidence: 66%
“…The promotion effect was dependent on expression of the pks island [ 15 ]. In a previous study from our laboratory, 88% of E. coli isolates from laboratory mice encoded pks genes and belonged to phylogenetic group B2 [ 16 ]. Our findings indicated that colibactin-encoding E. coli commonly colonize laboratory mice and may induce clinical and subclinical disease that may impact in vivo experimental results [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this report, we announce the draft genomes of five novel B2-phylotype E. coli strains isolated from the feces of two asymptomatic surveillance mice, the uterine fluid of a transgenic mouse, and from the blood of two experimental immunocompromised mice with sepsis housed under specific-pathogen-free conditions. We previously found all these strains except A4 were PCR-positive for the PKS genes clbA and clbQ and caused megalocytosis and γ-H2AX-detectable DNA damage in HeLa cells in vitro , suggesting colibactin activity by these organisms ([ 7 ]; our unpublished data). We briefly describe the features of these novel E. coli genomes in context to the previously sequenced genomes of NC101 and the PKS-containing septicemia- and meningitis-causing strains IHE3034 and A192PP ( 4 , 6 ).…”
Section: Genome Announcementmentioning
confidence: 89%